A Prospective Study of Percutaneous Vertebroplasty for Chronic Painful Osteoporotic Vertebral Compression Fracture. (2015) - Tan, Hong-Yu; Wang, Li-Min; Zhao, Liang; Liu, Yi-Lin; Song, Rui-Peng
Abstract : BACKGROUND: Percutaneous vertebroplasty (PVP) for patients with chronic painful osteoporotic compression fractures has not been extensively studied. OBJECTIVE: To prospectively evaluate the efficacy of PVP for patients with chronic painful osteoporotic vertebral compression fractures (VCFs). METHODS: Sixty-two consecutive patients with chronic painful osteoporotic VCFs for ≥3 months underwent PVP. All procedures were performed under local anesthesia. The outcomes were pain relief at one week, one month, three months, six months and one year, as measured by visual analogue scale, Oswestry Disability Index, Quality of Life Questionnaire of the European Foundation for Osteoporosis (QUALEFFO) and Roland Morris Disability Questionnaire scores. RESULTS: The PVP procedures were technically successful and well tolerated in all patients. Sixty-two patients underwent PVP on 92 vertebrae in 73 procedures three to five days after referral, and no 30-day mortality was observed. Compared with baseline scores, improvement in visual analogue scale, Oswestry Disability Index, QUALEFFO and Roland Morris Disability Questionnaire scores was significantly greater after PVP at one week (P<0.001), one month (P<0.001), three months (P<0.001), six months (P<0.001) and one year (P<0.001), and the number of patients using drugs for pain treatment was significantly reduced. Five new fractures were reported in five of 62 patients treated with PVP during follow-up. CONCLUSION: PVP is effective in patients with chronic painful osteoporotic VCFs. Pain relief after PVP was immediate, was sustained for one year and may be an important factor for reducing persistent pain.